Meat with edible coating: Acceptance, purchase intention and neophobia - Alves Mauricio, Raquel [UNESP]; Alvares Duarte Bonini Campos, Juliana [UNESP]; Tieko Nassu, Renata (Elsevier, 2022)
The acceptance of a new product depends on its sensory quality and consumers’ physiological and psychological aspects. The fear of consuming foods processed by new technologies is an example. This study aimed to investigate the overall acceptance and purchase intention of chitosan-coated beef and lamb meat in blind and informed conditions and to estimate the psychometric properties using the Food Technology Neophobia Scale (FTNS). Beef and lamb meat samples were evaluated for overall acceptance (1 = extremely disliked, 9 = extremely liked) and purchase intention (1 = certainly would not buy, 5 = certainly would buy). A questionnaire containing the Food Technology Neophobia Scale (FTNS) was applied, and sociodemographic data were collected, and 297 consumers participated in this study. For beef, chitosan-coated in the informed condition was the most accepted. In contrast, for lamb meat, the overall acceptance values of control and chitosan treatments in the blind condition were higher than the samples in the informed condition. However, cluster analysis indicated three clusters of consumers with different perceptions for both types of meat. The original FTNS showed factorial invariance, and the abbreviated scale (AFTNS) was used. The final AFTNS model showed good adjustment index (λ = 0.41 – 0.73; χ2 / gl = 3.5; CFI = 0.93; TLI = 0.90; RMSEA = 0.09) and had 8 items. For most consumers in this study, an absence of neophobia was observed (71.1%), indicating that the chitosan-coated meat would potentially be commerced.
Keywords: Chitosan; Confirmatory factor analysis; Consumer; Label; Sensory